Change in Organizational Structure Influences Perceived Leadership in a Dutch Radiotherapy Center - Swart RR; Jacobs MJ; Van Merode F; Boersma LJ (Journal of Healthcare Leadership, 2025)
Rachelle R Swart,1 Maria JG Jacobs,2 Frits Van Merode,3,4 Liesbeth J Boersma1 1Department of Radiation Oncology (Maastro), GROW Research Institute for Oncology and Reproduction, Maastricht University Medical Centre+, Maasstricht, the Netherlands; 2Tilburg School of Economics and Management, Tilburg University, Tilburg, the Netherlands; 3Care and Public Health Research Institute, Maastricht University, Maastricht, the Netherlands; 4Maastricht University Medical Centre+, Maastricht, the NetherlandsCorrespondence: Rachelle R Swart, Email rachelle.swart@maastro.nlPurpose: Healthcare organizations face challenges in balancing efficiency and innovation, known as ambidexterity. Leadership plays an important role, with transformational leadership driving innovation and transactional leadership supporting efficiency. The dominant leadership framework is the Full-Range Leadership Theory (FRLT), which identifies three leadership behaviors: transformational, transactional, and passive avoidant. Organizational structures, following Mintzberg, Pugh and Galbraith, including span of control (SoC), unit grouping, and lateral linkages, significantly influence leadership dynamics. This study examines the impact of structural changes on perceived leadership styles in a Dutch radiotherapy center (RTc) following the implementation of proton therapy, a radical innovation.Patients and Methods: A mixed-method approach combined leadership surveys, with data collected at three time points, before and after structural changes in 2022. The multifactor leadership questionnaire (MLQ) was distributed among the employees in November 2021, March 2022, and March 2023. Three interventions were introduced: (1) appointing dedicated team leaders (TLs) to improve information flow and reduce management SoC; (2) integrating a Patient Care (PC) manager into the advisory board to facilitate direct communication within the governance structure, including other hierarchical layers; and (3) adding a proton therapy manager as a liaison to improve coordination. Leadership perceptions were measured using the Multifactor Leadership Questionnaire (MLQ) at three time points (T1, T2, T3). The Independent-Samples Mann–Whitney U-Test (p< 0.05), was used to compare T1, T2, and T3, managers’ self-ratings with employee ratings, and scores between photon and proton treatment employees.Results: Transformational leadership significantly increased across all groups, with PC scores rising from 2.3 at T1/T2 to 2.5 at T3, and MT-PC scores from 1.8 at T1 to 2.4 at T3. Passive avoidant leadership significantly decreased (eg, MT-PC: 1.6 at T1 to 1.0 at T3). Transactional leadership showed less pronounced and non-significant changes. Photon therapy staff experienced earlier improvements in leadership perceptions, while proton therapy staff showed delayed but stronger shifts by T3.Conclusion: In this study, structural changes positively influenced leadership perceptions, supporting ambidexterity. Significant increases in transformational leadership and decreases in passive avoidant leadership align leadership styles with the dual demands of innovation and operational efficiency, demonstrating the importance of organizational design in healthcare leadership. Our findings show that healthcare management could use organizational structure changes to promote transformational leadership.Keywords: leadership, healthcare, radiotherapy, ambidexterity